Samuel Johnson - Bate, Walter Jackson, 1918-1952. (Washington : Counterpoint, 1998)
"In this biography - a work that won three of the most prestigious literary prizes this country offers - W. Jackson Bate delves deep into the character that formed Johnson's awesome intellect and fueled his prodigious output. The first great modern biography of Johnson, it confirms that his statements and judgments on literature, politics, religion, behavior - on all human experience - are as relevant in our age as when they were first uttered. This new edition brings a modern classic back into print and includes a new preface from the author."--BOOK JACKET.
Originally published: New York : Harcourt Brace Jovanovich, 1975.
Includes bibliographical references and index.
Keywords: Johnson, Samuel, -- 1709-1784.; Great Britain -- Intellectual life -- 18th century; Authors, English -- 18th century -- Biography; Lexicographers -- Great Britain -- Biography; Intellectuals -- Great Britain -- Biography